MANAJEMEN PONDOK PESANTREN TERHADAP PERKUMPULAN SANTRI KEDAERAHAN - Ahmad Khoiri (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
Pesantren in to face changing be prosecuted to do kontekstualisasi withoutmust to sacrifice it my gap its original character education institution andsocial religiousness. Pesantren must to order his weakness, that is with toapply it management the good education. pesantren's management be done inmerefungsionalisasi pesantren effort so that role and his contribute as actordevelopment the society is felt real. With such, pesantren to front to beexpected not only to play it its traditional function but must more than thatpesantren must to do tranformation that can to support quality resourcehuman (SDM) that of course orientationy into pesantren and out pesantrenwho continue to development and society development. Ability as fvepesantren on societyy that this tribe different until to appear it semanagatstruggle in societyy and to develop it potency and the existence all at once toshow its superiority. the mentioned Superiority putted to ability pesantrenjoin it intellectual intelligent, emotional, and enthuisiasmual.Key Word: Management, Pesantren's Cottage, Santri.